Convalescent plasma therapy: a promising coronavirus disease 2019 treatment strategy - Piyush, Ravikant (Open Biol, 2020)
The world is passing through a very difficult phase due to the coronavirus disease 2019 (COVID-19) pandemic, which has disrupted almost all spheres of life. Globally, according to the latest World Health Organization report (10 August 2020), COVID-19 has affected nearly 20 million lives, causing 728 013 deaths. Due to the lack of specific therapeutic drugs and vaccines, the outbreak of disease has spawned a corpus of contagious infection all over the world, day by day, without control. As the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a very rapid infection rate, it is essential to develop a novel ameliorative and curative strategy as quickly as possible. Convalescent plasma (CP) therapy is a type of adaptive immunity that has already been found to be effective in confronting several infectious diseases from the last two decades. For example, CP therapy was used in the treatment of viral-induced diseases like SARS-CoV epidemics, Middle East respiratory syndrome coronavirus (MERS-CoV) pandemics, Ebola epidemics and H1N1 pandemic. In this review, we have mainly focused on the therapeutic role of CP therapy and its neutralizing effect to fight against the COVID-19 outbreak.